An open-label, pilot study to evaluate the benefits of using lyophilized human milk-derived nutritional product (NeoLact 70 – 1.55 g) as an immune-nutritional supplement in premature infants discharged from NICU - R, Gowtham; Afza, Anisha; Shankar, Shankar; Subbanna, Lingaraju (Indian Journal of Child Health, 2021)
Background: Premature and low birth weight (LBW) infants are at increased risk of having inadequate growth in post-discharge periods. In this study, lyophilized human milk was used as an immune-nutrition supplement along with breastfeeding for a period of 1 month in preterm infants discharged from neonatal intensive care unit (NICU). Objectives: Primary objective was to assess the percentage change in serum immunoglobulins for the duration of supplementation, and secondary objectives were to correlate changes in immunoglobulins to number of episodes of infections including respiratory infections and diarrhea, requirement of antibiotics, weight gain, and episodes of feed intolerance during the study period. Methods: A total of 10 preterm and LBW infants were included in the study at the time of discharge from NICU after satisfying the inclusion and exclusion criteria. The serum immunoglobulins were estimated at baseline and at end of the study, other parameters such as episodes of infections, feed intolerance, and weight gain were recorded on the weekly follow-up visits. All the infants received supplementation with NeoLact 70 – 1.55 g on a TID frequency along with the regular breastfeeding for a period of 1-month post-discharge from NICU and were followed up on a weekly basis. Results: Ten infants completed the study, mean birth weight and gestational age were 1779.4±576 gm and 33.5±4.9 weeks, respectively. There was increase in immunoglobulins IgA, IgE, IgG, and IgM by 38.29%, 85.36%, 17.45%, and 48.25%, respectively, from baseline to end of study. None of the infants experienced feeding intolerance, diarrhea, abdominal distension, fever, respiratory infections, or rehospitalizations, none of the infants required antibiotics or probiotics during the study period. The average weight gain in the 1st, 2nd, 3rd, and 4th week of supplementation was 28.42 g/day, 31.57 g/day, 35.17 g/day, and 39.24 g/day, respectively, with a mean weight gain of 30.4 g/day achieved for the entire duration of the study. Conclusion: The immune-nutritional supplementation with lyophilized human milk (NeoLact 70 – 1.55 g) helps to ensure exclusive human milk diet post-discharge and reduce the risk of infections, diarrhea, and rehospitalization through the enhancement of immunoglobulins and ensuring optimal weight gain. However, these results should be confirmed through multicentric studies with larger sample size. Supplementation with NeoLact 70 – 1.55 g can clinically benefit premature and LBW infants post-discharge.